THE EFFECTIVENESS OF CAPACITY BUILDING TRAINING ON IMPROVING TEAMWORK IN KULONPROGO INDONESIA - Eliasa, Eva Imania; Baroroh, Kiromim; Lidyasari, Aprilia Tina (I-iECONS e-proceedings, 2023)
This research aims to improve teamwork through capacity building training for the youth of Pagerharjo Kulonprogo Village. The background of this research is based on the phenomenon in the field, the youth do not have good cooperation concepts and skills. Therefore, capacity building training is needed to improve cooperation. The training was aimed at BUMDes Pagerharjo youth who were taken with purposive sampling. The research approach used a research and development design with 4D techniques, namely define, design, develop, and disseminate. The research instrument used the Capacity Development Scale. The results showed 0.000 <0.05 there was a significant change in the improvement of teamwork in Pagerharjo youth between before and after being given Capacity Building Training both in terms of knowledge and cooperation skills. The output achieved is intellectual property rights and articles in published journals.